Multicriteria approach applied to knowledge management: A review - Goffi, Andreia dos Santos; Zarelli, Paula Regina; Mendes, Lígia (Seven Editora, 2023)
Purpose: This paper aims to propose a multicriteria knowledge management instrument, built from a comprehensive systematic review of the literature, to support decision-making. Design/methodology/approach: The study consists of a systematic review of 20 articles, resulting from the InOrdinatio Index Method or Methodi Ordinatio (Pagani et al., 2017). Findings: The use of the multicriteria approach as a tool in the evaluation or selection of methods or instruments for knowledge management resulted in 74 criteria, relevant to the definition of a knowledge management system considering the different scenarios. The findings demonstrate the complexity of a problem given the variety of criteria that can be used to assess or select different knowledge management systems. Additionally, it is possible to observe that there is no prioritization of one criterion when compared to another. Research limitations/implications: The criteria found with the application of the InOrdinatio Index Method may not cover all the literature regarding the research topic. Yet, it is believed that the findings provide a valuable understanding of the current situation in this research field. The study proposes several future research directions, on how to verify the adherence of the criteria found in decision making in knowledge management systems. Originality: To the best of the authors’ knowledge, no systematic literature review about Knowledge Management with the application InOrdinatio Index method has previously been published in academic journals. DOI:https://doi.org/10.56238/alookdevelopv1-027